Frailty in the elderly: prevalence and associated factors - Jair Almeida Carneiro; Rafael Rodrigues Cardoso; Meiriellen Silva Durães; Maria Clara Araújo Guedes; Frederico Leão Santos; Fernanda Marques da Costa; Antônio Prates Caldeira
ABSTRACT Objective: to know the prevalence and factors associated with frailty in elderly assisted by the Centro Mais Vida de Referência em Assistência à Saúde do Idoso (Mais Vida Health Reference Center for the Elderly) in the North of Minas Gerais, Brazil. Method: cross-sectional study, with sampling by convenience. Data collection occurred in 2015. Demographic and socioeconomic variables, morbidities, use of health services and the score of the Edmonton Frail Scale were analyzed. The adjusted prevalence ratios were obtained by multiple analysis of Poisson regression with robust variance. Results: 360 elderly aged 65 or older were evaluated. Frailty prevalence was 47.2%. The variables associated with frailty were the following: advanced age elderly, who live without a partner, have a caregiver, present depressive symptoms, osteoarticular disease, as well as history of hospitalization and falls in the last twelve months. Conclusion: knowledge of factors associated with frailty allows development of health actions aimed at the elderly.